Effective business letters and communication - Macabuhay, Cynthia H. (Mandaluyong City, Philippines : National Book Store, 2010)
The Third edition features the principles of business english, composition and business ethics. Basic approaches to effective communication are given which are applicable to business operations in the Philippine setting.
Includes bibliographical references.
Keywords: BUSINESS WRITING